Training of trainers on the establishment of Community-Based Breeding Programme for small ruminants in Uganda: Strengthening competence in improved health and feeding, reproductive management, genetic improvement, and marketing - Recha, John W.M.; Haile, Aynalem; Getachew, Tesfaye; Barungi. Julian; Ilakut, Ben; Okonya, Joshua; Gitau, Angela; Radeny, Angela (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
The Association for Strengthening Agricultural Research in Eastern and Central Africa (ASARECA) is an intergovernmental sub-regional organization of the National Agriculture Research Systems of fifteen Member States namely: Burundi, Cameroun, Central African Republic, Democratic Republic of Congo, Eritrea, Ethiopia, Madagascar, Kenya, Republic of Congo, Rwanda, Sudan, Somalia, South Sudan, Tanzania and Uganda. ASARECA is mandated to coordinate and convene human, physical, financial and institutional capital to implement Agricultural Research for Development (AR4D) initiatives in Eastern and Central Africa (ECA). ASARECA is implementing the Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) Project in partnership with the Alliance of Bioversity International and CIAT - the lead institution for the project. The AICCRA project is funded by the World Bank and aims to strengthen the technical, institutional, and human capacity needed to enhance transfer of climate-relevant information, decision-making tools, and technologies in support of scaling efforts in IDA-eligible countries in Africa. The project focuses on 4 major components namely: (i) knowledge generation and sharing through development of climate-informed agricultural advisory services and decision-making tools; (ii) strengthening partnerships for delivery of climate-smart innovations in agriculture; (iii) validating climate-smart agriculture innovations through piloting; and (iv) project management. The training is organized under the auspices of ASARECA’s AICCRA project and it contributes to AICRRA project IPI 3.2 on gender-smart climate information services and gender-smart agriculture technologies reaching women through customized programs targeting their interests.